1987
DOI: 10.1139/y87-373
|View full text |Cite
|
Sign up to set email alerts
|

The 1986 Borden Award Lecture. The role of the kidney in amino acid metabolism and nutrition

Abstract: Measurement of the arteriovenous differences for free amino acids across rat kidney reveals that glycine and citrulline are removed and serine and arginine are added to the circulation. In addition, glutamine is taken up in large quantities by kidneys of animals that need to excrete large quantities of acid (e.g., diabetic animals, NH4Cl-fed animals, and animals fed a high protein diet). Glutamine is the major precursor of urinary ammonia and thus renal glutamine metabolism plays a key role in acid-base homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
5

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 3 publications
3
18
0
5
Order By: Relevance
“…Interestingly, renal citrulline uptake was considerably higher than the rate at which citrulline was released from the splanchnic area, supporting that also other processes than glutamine metabolism provide citrulline for renal arginine synthesis (Castillo et al 1996). In line with earlier findings in humans (Brosnan 1987; Tizianello et al 1980, 1985), our data show a net renal release of serine into the systemic circulation. In contrast to our data, those studies also showed a significant renal uptake of glycine, which was interpreted as evidence for conversion of glycine to serine in the kidneys.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Interestingly, renal citrulline uptake was considerably higher than the rate at which citrulline was released from the splanchnic area, supporting that also other processes than glutamine metabolism provide citrulline for renal arginine synthesis (Castillo et al 1996). In line with earlier findings in humans (Brosnan 1987; Tizianello et al 1980, 1985), our data show a net renal release of serine into the systemic circulation. In contrast to our data, those studies also showed a significant renal uptake of glycine, which was interpreted as evidence for conversion of glycine to serine in the kidneys.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to our data, those studies also showed a significant renal uptake of glycine, which was interpreted as evidence for conversion of glycine to serine in the kidneys. A possible explanation for this discrepancy is that glycine is probably also supplied to the kidneys from sources other than direct uptake from the bloodstream (Brosnan 1987; Dejong et al 1998; Pitts and MacLeod 1972) This, in turn, offers an additional explanation why glycine uptake accounts for only 30 % of the net renal release of serine (van de Poll et al 2004). On average, 1.5 g glycine is taken up by the human kidneys per day (Tizianello et al 1980), followed by a release of 4 g serine per day (Tizianello et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes present in the intestinal epithelium convert glutamine to glutamate and then via ornithine to citrulline [23]. The kidney then metabolizes gut citrulline to arginine [35]. We cannot explain the lack of NO synthesis by stimulated macrophages incubated in culture medium devoid of both arginine and glutamine but supplemented with citrulline by the lack of renal tissue in our cell cultures, since RAW 264.7 macrophages have been shown to convert citrulline to arginine in vitro [36].…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, enzymes involved in serine glycine conversion, glycine degradation by glycine cleavage enzyme, and glutathione synthesis from glycine were exclusively expressed in liver and kidney. Therefore, we predict that serine may be involved in an inter-organ transport in which adipose synthesizes and releases serine as the precursor of glycine for liver and kidney [32], [35], [36] (Figure S6C). Evidently, this novel pathway is still hypothetical and needs to be experimentally validated using isotope labeled compounds.…”
Section: Resultsmentioning
confidence: 99%